Prevention and Treatment of Incontinence-Associated Dermatitis (IAD): Contributes of Nursing Intervention - Tavares, Ana; Ramos, Ana; Lopes, Manuel; Mendes, Felismina; Fonseca, César; Parreira, Pedro (My University, 2017)
Incontinence-Associated dermatitis (IAD) is a combination of skin changes caused by the presence of confluent moisture, being characterized by prolonged skin exposure to elimination. НLs is a rather frequent condition, taking into account that there is a sLJnLficDnt proportion of people, most of whom are aged 65 years or over and are admitted to acute or long-term care, suوٴerLnJ from urinary and/or fecal incontinence [1]. Typically it is recognized as an LnflDmmDtLon of the skin surface characterized by redness (skin rush), which mainly Dوٴects the region of the thighs, buttocks and scrotum, in males and large lips in females [1,2]. НLs type of injury translates the reaction of the skin to the aggressor agent, immediately compromising its ability to act as a protective barrier [3]. If IAD is not LdentLfied and treated in a timely manner, this redness and/or rush may progress rapidly to the local formation of abrasions and vesicular lesions that with prolonged exposure to risk factors may trigger an infectious process with high severity [4]. A cycle begins where a progressive increase of local LnflDmmDtLon and loss of cutaneous integrity is observed
Keywords: Incontinence-Associated Dermatitis; Nursing